Two-dimensional DOA estimation of unitary transformation matrix reconstruction based on L-shaped array - Xiu WANG; Qing CHANG; Yaoli WANG (Dianxin kexue)
The estimation of the direction of arrival of two-dimensional space signals is the key problem in the field of array antennas.Although the traditional two-dimensional MUSIC algorithm has high precision,it needs two dimensional spectrum peak search and has a large amount of operation.A two-dimensional DOA estimation algorithm for L-shaped array was proposed.The output matrix was transformed from a complex value matrix to a real value matrix by matrix reconstruction and a unitary transformation matrix.This method could directly get the elevation angle of the target without conversion,which greatly reduced the amount of operation.Compared with the matrix enhancement and matrix pencil algorithm for L-shaped array,this algorithm could estimate more targets’DOA.The results of simulation show that the algorithm has a high accuracy of DOA estimation.